Implementasi Content Planning untuk Meningkatkan Social Presence Akun Instagram “X” - Elisabeth Meylani; Oscar Karnalim (Journal of Smart Technology and Engineering, 2026)
Instagram is widely used by educational institutions as a digital communication platform to enhance interaction and social presence. However, unstructured content management may result in low audience engagement. This study aims to analyze the implementation of content planning in improving the social presence of Instagram accounts. A descriptive quantitative method was applied using Instagram Insights data as the primary source. The analysis focused on content themes and formats using engagement rate as the evaluation metric. The results indicate that structured content planning, particularly activity-based and short video content, significantly improves audience engagement. These findings suggest that effective content planning plays an important role in strengthening the social presence of educational institution Instagram accounts.